„HERACLEA LYNCESTIS“ FROM VANJA ANGELOVA OR: ABOUT ANCIENT HISTORY, TOUGHNESS, HUMANITY AND INFINITY - Chochorovska, Lusi Karanikolova (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
This text is an attempt for elementary simplification of the poetry of the anthology “Heraclea Lyncestis” from Vanja Lazarova in Macedonian language.  The accent is placed on the structure of the anthropology, whose songs are inspired by Macedonia and Macedonian history. The main trump in this poetry, according to our opinion, is the stone metaphor, which is related to Macedonian history and Macedonian soil, in the past and today.